The Efficiency and Performance Evaluation of Government-Linked Companies (GLCs) in Malaysia using Data Envelopment Analysis - Khairul Rizuan Suliman; Mohd Danial Afiq Khamar Tazilah; Kah Fai Liew; D Karunanithy Degeras (International Journal of Supply Chain Management, 2020)
Efficiency is a vital criterion in global competitive business and sustainable growth. Efficiency has always been reflected in company’s performance based on the existing input or resources available against the optimum output generated. A highly strong organizations capability will attract higher revenue and more investors to the company. The purpose of this study is to evaluate, compare and rank the overall efficiency based on annual report of companies in Malaysia stock market by using Data Envelopment Analysis (DEA). The analysis is carried out on 15 government-linked companies (GLCs) where cross-sectional data between periods of 2013 to 2017 were evaluated. Three efficiency input were considered including return on assets, return on equity and tobin’s q where the outcome or outputs were profitability. The results indicate the significance to the investors as the overall efficiency of the companies is ranked according to several years of reports using the DEA model. The implication of this research would benefit the organizations to perform better.